Managing an Electricity Shortfall : A Guide for Policymakers - Energy Sector Management Assistance Program (World Bank, Washington, DC, 2017)
Supply-demand tension has taken its toll in various countries around the world over the last several years. Governments and utilities have faced gaps between electricity supply and demand, which has led to blackouts and load shedding and translated into electricity shortfalls. While countries look to avoid the prospects of supply shortages by, inter alia, strengthening planning capacity and working to achieve a sounder and more sustainable electricity sector, the possibility of shortages in the future remains. This document summarizes the framework for action and a broad menu of options available to policymakers to bridge a supply demand gap in the short- to medium-term.